2005
DOI: 10.1117/12.594579
|View full text |Cite
|
Sign up to set email alerts
|

Corneal injury to ex vivo eyes exposed to a 3.8-micron laser

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. The author hereby certifies that the use of any copyrighted material in the thesis manuscript entitled: Corneal Injury to Ex-vivo Eyes Exposed to a 3.8 Micron Laserbeyond brief excerpts is with the permission of the copyright own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Studies have also shown enucleated rabbit eyes sustained in culture retain wound healing dynamics and are comparable to live rabbit eye model in terms of laser radiation exposure. (McCally et al, 1992; McCally and Bargeron, 2000; Kabosova et al, 2003; Fyffe, 2005) The use of this ex vivo organ culture can help reduce the need for animals in experiments. (Toropainen, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown enucleated rabbit eyes sustained in culture retain wound healing dynamics and are comparable to live rabbit eye model in terms of laser radiation exposure. (McCally et al, 1992; McCally and Bargeron, 2000; Kabosova et al, 2003; Fyffe, 2005) The use of this ex vivo organ culture can help reduce the need for animals in experiments. (Toropainen, 2007).…”
Section: Discussionmentioning
confidence: 99%